2022
DOI: 10.1021/acs.jpcb.2c01947
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Dynamics upon Pressure-Induced Liquid–Liquid Phase Separation in a Water–Lysozyme Solution

Abstract: Employing X-ray photon correlation spectroscopy, we measure the kinetics and dynamics of a pressure-induced liquid−liquid phase separation (LLPS) in a water−lysozyme solution. Scattering invariants and kinetic information provide evidence that the system reaches the phase boundary upon pressure-induced LLPS with no sign of arrest. The coarsening slows down with increasing quench depths. The g 2 functions display a two-step decay with a gradually increasing nonergodicity parameter typical for gelation. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…However, when adding H2O2, we observed remarkable changes in the dynamic properties of condensates (Fig. 4g): [PrP:Cu 2+ +H2O2] condensates/aggregates were characterized by super diffusive ( > 1) viscoelastic relaxation indicating network fluctuations in the condensates, likely via liquid-to-solid transition during gelation/hardening 52,53 . The loss of molecular diffusion (FRAP data, Fig.…”
Section: X-ray Photon Correlation Spectroscopy Reveals H2o2-induced D...mentioning
confidence: 99%
“…However, when adding H2O2, we observed remarkable changes in the dynamic properties of condensates (Fig. 4g): [PrP:Cu 2+ +H2O2] condensates/aggregates were characterized by super diffusive ( > 1) viscoelastic relaxation indicating network fluctuations in the condensates, likely via liquid-to-solid transition during gelation/hardening 52,53 . The loss of molecular diffusion (FRAP data, Fig.…”
Section: X-ray Photon Correlation Spectroscopy Reveals H2o2-induced D...mentioning
confidence: 99%
“…43,69,70 Recently, X-ray photon correlation spectroscopy (XPCS) was applied to study also the kinetics and dynamics of pressure-induced LLPS formation in a concentrated water− lysozyme solution (at 240 g mL −1 , 0.5 M NaCl) as a function of quench-depth into the two-phase region. 72 XPCS is a powerful tool to investigate dynamic processes at nanometer length scales and microsecond-to-second time scales in soft matter systems. The sample dynamics is reflected by the intensity fluctuations of the recorded speckle patterns of the scattered synchrotron X-ray beams.…”
Section: Volume-sensitive Conformational Changes Phase Transitions An...mentioning
confidence: 99%
“…No glass-like behavior (i.e., complete arrest) could be observed as in deep temperature-quench experiments. 72 Mukherjee et al and other groups have shown that LLPS of disordered amyloidogenic peptides, such as α-synuclein, may occur in the nucleation step of aggregation and fibril formation, which offers an alternative noncanonical aggregation pathway next to the nucleation and growth route of amyloid-forming peptides. 73 The liquid-like droplets then gradually undergo an irreversible liquid-to-solid phase transition forming amyloidlike hydrogels entrapping oligomers and fibrils.…”
Section: Volume-sensitive Conformational Changes Phase Transitions An...mentioning
confidence: 99%
See 1 more Smart Citation
“…XPCS has been demonstrated for a broad range of soft condensed matter systems [29,30], including amorphous water where a liquid-liquid transition was observed in the ultraviscous regime [31]. However, due to experimental difficulties in working with radiation-sensitive samples, XPCS of protein systems became possible only recently with optimized experimental procedures [32][33][34][35][36][37][38][39][40].…”
mentioning
confidence: 99%